Entrepreneurial education on skills acquisition for university graduates in Nigeria - Mohammed, Idris Abdullahi (International Journal of Evaluation and Research in Education (IJERE), 2022)
The rate of unemployment among graduates of tertiary institutions in Nigeria is still on the alarming level, with a large number of graduates relying on government jobs. Interaction with university graduates discovered that most of them did not possess the adequate skills and knowledge needed to personally engage in entrepreneurial ventures. The yardstick that will lead to the realization of the objectives of entrepreneurial education is not translated into practical realities, right from the policy implementation to the transmission of the knowledge and skills desirable for practical application in the real-life business. Hence, this study aimed at providing the graduates with essential skills and knowledge required for empowering them to establish businesses of their own. This, therefore, enabled the graduates to become self-employed and self-reliant for a sustainable livelihood, and socio-economic development in the society. Entrepreneurial education is determined to inculcate the entrepreneurial spirits, amongst especially the graduates to start thinking of setting up their own businesses for self-employment instead of relying on the government for the white-collar jobs. Thus, this study will highlight the impact of entrepreneurial education on skills acquisition for preparing the graduates into a successful occupational career. This paper is a library-based collection of data using textbooks, journal articles, and various research websites from the internet, by identifying and gathering relevant and reliable information that serves the purpose for which it is intended. The study has 4 objectives in the form of questions the answer to which vividly indicates the pertinent nature and benefits of entrepreneurship on entrepreneurial skills acquisition by the graduates in setting-up their own businesses. The study portrayed that entrepreneurship education can provide indispensable entrepreneurial skills required by the graduates to pursue and engage in entrepreneurial activities. In conclusion, this study is capable of providing the graduates with the knowledge and skills necessary to identify, determine and pursue new business opportunities for self-employment and self-reliance, which lead to the realization of economic self-independence in the society on one hand and the country at large on the other hand.Â Â